Community Service on Implementing Learning Media as Support Technology for Neurodivergent Children Community in Surabaya - Paramitha, Melvie; Hari, Yulius; Yanggah, Minny Elisa; Santi, Chitra (Asia Pacific Journal of Management and Education (APJME), 2024)
Neurodivergent children may have conditions such as autism spectrum disorder, attention deficit hyperactivity disorder (ADHD), dyslexia, or other learning differences. These children often experience challenges in communication, social interaction, and academic performance, requiring tailored support in educational settings. This community service program is partnering with ELMO a community for neurodivergent children. The goals of this program are to develop an assistive learning media eLearning and also technology transfer. The result shows a positive impact and can satisfy both the partner and parents of the neurodivergent children to track their studies.